Pengaruh Substitusi Tepung Sagu (Metroxylon sagu R) pada Terigu terhadap Karakteristik Kue Kering - Aghnia Rahmawati; Kelik Putranto; Anne Tristianne (Ma'soem University, 2023)
There are so many kinds of foods made of wheat flour. The dependency on wheat flour will be a problem in the future because wheat as raw material could not be cultivated in Indonesia. The Government and private companies have to import wheat from other countries to fulfil people need on wheat flour which rise from year to year. Wheat flour as raw material in food production contain high glycemic value that is not good for our health. One of the alternatives to replace wheat flour is sago flour, because it contains high carbohydrate and other nutrition. The most important thing is that sago flour is gluten free. Sago flour is suitable for cookies making. Research had been done at the Laboratory of Agriculture Faculty UICM and at Chemistry Laboratory of Agriculture Faculty Ma’soem University. The objective of the research was to find out the effect of sago flour substitution to wheat flour on the characteristics of cookies. The experimental method was applied in this research with 8 treatments and repeated 3 times. The treatments were sago substitution of 0%(A), sago substitution of 10%(B), sago substitution of 20% (C), sago substitution of 30%(D), sago substitution of 40% (E), sago substitution of 50% (F), sago substitution of 60% (G), and sago substitution of 70% (H). The organoleptic test was applied on colour, taste, aroma and texture. Result of the research showed that treatment H produced cookies with the best characteristic according to colour and aroma.